Isotopic composition of oxygen in snow-and-firn thickness on the Eastern peak of Elbrus, the Caucasus - Yu. N. Chizhova; V. N. Mikhalenko; Yu. K. Vasil’chuk; N. A. Budantseva; A. V. Kozachek; S. S. Kutuzov; I. I. Lavrentiev (Лëд и снег, 2019)
The isotopic composition of oxygen of the snow-and-firn and snow thickness on the Eastern peak of Elbrus had been studied. In 2006-2008, a number of snow samples were taken in the near-peak area of Elbrus to analyze the isotopic composition of them. The drilling was performed at the crater of the Eastern peak in 2006 (64 samples) while in 2017 the samples were taken from snow pit (25 samples). Another core to a depth of 23.8 m was extracted at the Western Plateau (118 samples) for the purpose to compare local 518О values with samples from the Eastern peak. The δ18О values in the snow-and-firn thickness from the crater of the Eastern peak vary from -6.8 to -19.41 %o with the average value of -12.61 %o. It was revealed that snow layers with extremely low values of δ18О (down to -30 %) found on the eastern slope were absent on the western plateau. The loss of part of the annual isotope precipitation signal due to the winter extra light horizons could be caused by two reasons: wind drift of the freshly deposited snow, as well as the absence of part of the winter snowfalls with isotope-light precipitation at altitudes higher 5300 m. Seasonal variations of δ18О values, equal to 12 % and found in the snow-and-firn thickness on the Eastern peak, indicate that formation of the isotopic characteristics of snow is determined here by the equilibrium Rayleigh condensation and this is associated with the annual amplitude of the air temperature by a coefficient of 0.6 %o/°C. In the isotopic record obtained on the Western plateau of Elbrus, the relationship of values δ18О with the condensation temperature may be disturbed due to the frequent change of the main moisture-bearing air masses. This leads to significantly different δ18О values in precipitation at the same temperatures (the connection of seasonal δ18О values with the annual amplitude of air temperature varies from 0.3 to 1.12 %о/°С).